Inverse Kinematics Solution for a 6-Degree-of-Freedom Robotic Manipulator Based on FABRIK - YEM, J.; CHAY, T.F. (Journal of Engineering and Technology (JET), 2022)
This paper aims to present a novel algorithm to solve the inverse kinematics (IK) problem of a 6 Degree-of-Freedom (DOF) industrial robotic manipulator based on FABRIK (Forward And Backward Reaching Inverse Kinematics). The algorithm calculates and locates the joint position for every joint of the robotic manipulator in Cartesian space to bring the end-effector to the desired target position. Based on the obtained joint positions, the rotational angle for each joint is then calculated to complete the IK solutions. The algorithm is tested for its feasibility and accuracy in MATLAB Robotic Toolbox. The results show that with an average of 13 iterations of computing, the joint positions are obtained with an average error of 0.001256 mm in Cartesian space. The algorithm presented in this paper yields high accuracy with fewer iterations of computing thus offering a new way to solve the IK problem of industrial robotic manipulators.